Engineering Antiviral Vaccines - Zhou, Xingwu (ACS Nano, 2020)
Despite the vital role of vaccines in fighting viral pathogens, effective vaccines are still unavailable for many infectious diseases. The importance of vaccines cannot be overstated during the outbreak of a pandemic, such as the coronavirus disease 2019 (COVID-19) pandemic. The understanding of genomics, structural biology, and innate/adaptive immunity have expanded the toolkits available for current vaccine development. However, sudden outbreaks and the requirement of population-level immunization still pose great challenges in today’s vaccine designs. Well-established vaccine development protocols from previous experiences are in place to guide the pipelines of vaccine development for emerging viral diseases. Nevertheless, vaccine development may follow different paradigms during a pandemic. For example, multiple vaccine candidates must be pushed into clinical trials simultaneously and manufacturing capability must be scaled up in early stages. Factors from essential features of safety and efficacy, manufacturing, and distributions, to administration approaches, are taken into consideration based on advances in materials science and engineering technologies. In this review, we present recent advances in vaccine development by focusing on vaccine discovery, formulation, and delivery devices enabled by alternative administration approaches. We hope to shed light on developing better solutions for faster and better vaccine development strategies through the use of biomaterials, biomolecular engineering, nanotechnology, and microfabrication techniques.